2018
DOI: 10.1017/s0885715618000623
|View full text |Cite
|
Sign up to set email alerts
|

Evolution in the structure of akaganeite and hematite during hydrothermal growth: anin situsynchrotron X-ray diffraction analysis

Abstract: Synchrotron X-ray diffraction was used to monitor the hydrothermal precipitation of akaganeite (β-FeOOH) and its transformation to hematite (Fe2O3) in situ. Akaganeite was the first phase to form and hematite was the final phase in our experiments with temperatures between 150 and 200 °C. Akaganeite was the only phase that formed at 100 °C. Rietveld analyses revealed that the akaganeite unit-cell volume contracted until the onset of dissolution, and subsequently expanded. This reversal at the onset of dissolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…The conversion from Fh is the most common pathway for Hm formation in low-T natural systems (Cornell and Schwertmann, 2003;Lagroix et al, 2016). Although prior researchers have precipitated hydrohematite as a transient intermediate reactant (Peterson et al, 2018), for the first time, we successfully synthesized hydrohematite as a final metastable product from fresh two-line Fh gel. TRXRD revealed that when Fh gels were adjusted to pH 9-12 and heated at moderately low T (80-170 °C), Fe-deficient hydrohematite initially nucleated with Fe occ ∼0.50 (Fig.…”
Section: Formation Of Hydrohematitementioning
confidence: 99%
“…The conversion from Fh is the most common pathway for Hm formation in low-T natural systems (Cornell and Schwertmann, 2003;Lagroix et al, 2016). Although prior researchers have precipitated hydrohematite as a transient intermediate reactant (Peterson et al, 2018), for the first time, we successfully synthesized hydrohematite as a final metastable product from fresh two-line Fh gel. TRXRD revealed that when Fh gels were adjusted to pH 9-12 and heated at moderately low T (80-170 °C), Fe-deficient hydrohematite initially nucleated with Fe occ ∼0.50 (Fig.…”
Section: Formation Of Hydrohematitementioning
confidence: 99%
“…Akaganeite, schwertmannite, and jarosite can undergo transformation to hematite in both aqueous solution and through solid-state transformation. Akaganeite transforms to hematite via a dissolutionreprecipitation mechanism at ambient (~28 • C) [35] and hydrothermal (70-200 • C) [36,37,[121][122][123][124] conditions. The solution pH and the presence of other solutes are important parameters that govern akaganeite transformation [121], with goethite forming instead of hematite at pH > 12.…”
Section: Quantitative Measure Of Mineral Productionmentioning
confidence: 99%
“…The solution pH and the presence of other solutes are important parameters that govern akaganeite transformation [121], with goethite forming instead of hematite at pH > 12. Akaganeite transformation to hematite in hydrothermal systems sometimes precedes with the early formation of hydrohematite, an Fe-deficient, hydroxyl (-OH)rich hematite phase [124]. Akaganeite can also transform to jarosite at lower pH conditions (<pH 4.5) in the presence of sulfate [92].…”
Section: Quantitative Measure Of Mineral Productionmentioning
confidence: 99%
“…The composition is in agreement with the previous experimental results documented on minimum concentrations of monovalent Fe(III) ions at pH 8.2, which supported maximum formation of hematite [ 32 ]. Akaganeite has also been characterized as the first phase formed at 100 °C, which changed to an OH-rich and Fe-deficient hydrohematite in situ [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…The thermal transformation of the Fe 2 O 3 _Na-70 and Fe 2 O 3 _NH-70 precipitates was compared by DTA/TG curves ( Figure 6 ). The temperature between 150 and 200 °C is sufficient for rapid conversion of FeOOH polymorphs and may, therefore, involve goethite and akageneite dehydroxylation [ 33 ].…”
Section: Resultsmentioning
confidence: 99%